A novel polysaccharide isolated from mulberry fruits (Murus alba L.) and its selenide derivative: structural characterization and biological activities. Issue 6 (31st May 2016) - Chen, Chun; Zhang, Bin; Fu, Xiong; Liu, Rui Hai
Abstract : A novel polysaccharide (MFP3P) was isolated from Murus alba L. through the hot water extraction method followed by chromatographic purification. Abstract : A novel polysaccharide (MFP3P) was isolated from Murus alba L. through the hot water extraction method followed by chromatographic purification. The chemical structure of MFP3P was elucidated by acid hydrolysis, Smith degradation and methylation analysis, along with FT-IR, GC-MS, 1 H and 13 C NMR spectroscopy. Its morphological properties were further characterized by SEM and AFM. The selenide of the polysaccharide (MFP3P-Se) was obtained by the Na2 SeO3 /BaCl2 method. The antioxidant properties showed that MFP3P-Se exhibited higher peroxy radical-scavenging capacity than MFP3P in vitro . Moreover, MFP3P-Se had more significant hypoglycemic effects than MFP3P through promoting pancreatic cell proliferation and increasing glucose metabolism and insulin secretion.